An audit of the effect of case selection on compliance with a 30-minute audit standard for decision-to-delivery interval at category 1 caesarean section. (November 2021) - Kinsella, S.M.
Highlights: Audit of decision-to-delivery interval at caesarean section is promoted in UK units. In clinical practice, urgency of caesarean section may change after the decision. For audit, caesarean urgency should be recorded at the time of decision for delivery. For audit, separately report cases of failed operative vaginal delivery in theatre. Abstract: Background: Our hospital has an audit standard that ≥90% of women having category 1 (emergency) caesarean section should have a decision-to-delivery interval (DDI) ≤30 min. This audit aimed to identify potential influences of case selection on compliance. Methods: A prospective audit of category 1 caesarean section recorded urgency at time of decision for surgery and any urgency changes, as well as whether caesarean section followed failed operative vaginal delivery in the operating theatre. Results: Among 405 women, 158 women had failed operative vaginal delivery in the operating theatre followed by caesarean section, 247 had the delivery decision made in the labour room, 43 had a change in urgency. Depending on case inclusion, the proportion of women with DDI room, and 43 >30 min ranged between 8.3% (30/362; no urgency change, failed operative vaginal delivery included) and 21.9% (54/247; change in urgency, failed operative vaginal delivery excluded). The proportion of women with a DDI >30 min was 18.5% (42/227) if the decision for category 1 caesarean section was made in the labour delivery room (excluding cases of failed operative vaginal delivery). Conclusions: Compliance with an audit standard for (DDI) at category 1 caesarean section is markedly influenced by the inclusion criteria. For comparability with other publications, it is suggested urgency should be reported as that applied at the point of decision for caesarean section, however, category 1 caesarean section cases following failed operative vaginal delivery in the operating theatre should be identified and reported separately.